ENHANCING AUDITOR PROFESSIONAL SKEPTICISM: THE ROLE OF INDEPENDENCE, EXPERIENCE, LEADERSHIP STYLE, AND COMPETENCE - Yessie, Afly (Jurnal Akuntansi Bisnis, 2026)
Background: Professional skepticism is essential for auditors in completing their tasks. Objective: This study examines the effect of independence, experience, leadership style, and competence on auditor professional skepticism. Research Methods: This research was conducted at a Public Accounting Firm in South Jakarta, Indonesia. The number of samples was determined by random sampling method, with the total number of samples are 100 respondents. The data analysis technique used is Multiple Linear Regression using SEM-PLS. Research Results: The results of this study indicate that auditor independence and leadership style do not affect auditor professional skepticism. However, auditors' experience and competence affect auditors' professional skepticism. This suggests the need to emphasise developing work experience, increasing competence, and fostering leadership styles that strengthen auditor skepticism. In practice, it can be improved by conducting training, career coaching, and leadership support for auditors to ensure that they have sufficient competence and experience and solid skepticism in evaluating information. Originality/Novelty of Research: This study integrates four factors, namely independence, experience, leadership style, and competence, in explaining professional skepticism among auditors. This study explicitly examines “leadership style” in this context.